Weathering the Storm: Tax as a Component of Financial Capability - Toni Chardon (Australasian Accounting, Business and Finance Journal, 2011)
In a time of global economic uncertainty, maintaining a financial environment where consumers are protected from risk and continue to have opportunities to create wealth should be critical for governments, business and administrators. A financially capable population could therefore be the key to avoiding the crises of the past and getting back to economic prosperity. The Australian Government has recognised that for those with the lowest levels of financial literacy, specific financial literacy programs can equip them with the appropriate financial skills and knowledge to ensure that they can make well informed decisions and be less vulnerable to scams and market risks (Commonwealth Department of Treasury 2006). However, if these programs are to be successful it is imperative that all aspects of financial capability have been considered. This paper will argue that there is a research gap in terms of what components should be considered (and therefore measured) as part of financial capability and specifically that taxation and to a lesser extent, superannuation have largely been excluded in both the measurement and education program aspects. If taxation and superannuation are not seriously considered as important components of financial capability, there could not only be risks to an individual’s financial position, but also significant risks to the broader economy, consumer wealth and the revenue base through poor financial capability.
Keywords: Financial Planning; Relationships; Ethics; Trust; Business Relationships; Relationship Quality